High‐Temperature Optical Characterization of GaN‐Based Light‐Emitting Diodes for Future Power Electronic Modules. Issue 7 (30th December 2019) - Madhusoodhanan, Syam; Sabbar, Abbas; Atcitty, Stanley; Kaplar, Robert; Mantooth, Alan; Yu, Shui-Qing; Chen, Zhong
Abstract : High‐temperature optical analysis of three different InGaN/GaN multiple quantum well (MQW) light‐emitting diode (LED) structures (peak wavelength λ p = 448, 467, and 515 nm) is conducted for possible integration as an optocoupler emitter in high‐density power electronic modules. The commercially available LEDs, primarily used in the display ( λ p = 467 and 515 nm) and lighting ( λ p = 448 nm) applications, are studied and compared to evaluate if they can satisfy the light output requirements in the optocouplers at high temperatures. The temperature‐ and intensity‐dependent electroluminescence (T‐IDEL) measurement technique is used to study the internal quantum efficiency (IQE) of the LEDs. All three LEDs exhibit above 70% IQE at 500 K and stable operation at 800 K without flickering or failure. At 800 K, a promising IQE of above 40% is observed for blue for display (BD) ( λ p = 467 nm) and green for display (GD) ( λ p = 515 nm) samples. The blue for light (BL) ( λ p = 448 nm) sample shows 24% IQE at 800 K. Abstract : A stable peak internal quantum efficiency and a lower injected current density in the operating temperature range are suitable options for the selection of light‐emitting diodes (LEDs) to integrate into high‐temperature optocoupler. This study analyzes the possibility of InGaN/GaN multiple quantum well (MQW) LED structures for potential integration as an optocoupler emitter in future power electronic modules.